The Role of Agronursing in Managing Hypertension Among Farmers - Kurniyawan, Enggal Hadi; Khodijah Damanhuri; Siti Nur Aisyah; Halimatus Sufiyani; Afandi, Alfid Tri; Kurniawan, Dicky Endrian; Nur, Kholid Rosyidi Muhammad (International Health Sciences Journal, 2026)
Hypertension remains a significant public health challenge among agricultural workers, particularly in rural areas with limited access to healthcare services. The unique occupational and environmental risk factors faced by farmers, such as heavy physical workload, prolonged heat exposure, unhealthy dietary habits, and low health literacy, contribute to the high prevalence of hypertension in this population. Agronursing, an integrative approach that combines nursing practices with agrarian contexts, has emerged as a promising model for managing hypertension in farming communities. This literature review evaluates the effectiveness of agronursing interventions in reducing blood pressure and improving health outcomes among farmers. A comprehensive literature search across four databases (Semantic Scholar, PubMed, Springer, and ScienceDirect) yielded 10 eligible studies published between 2020 and 2025. These studies explored various interventions, including plant-based diet modifications, community-led health education, involvement of local health cadres, non-pharmacological therapies such as slow stroke back massage, and nurse-led hypertension management. Findings indicate that agronursing interventions significantly contribute to lowering blood pressure, increasing health awareness, and promoting sustainable lifestyle changes. The most successful interventions were those that integrated cultural sensitivity, utilized local resources, and involved trained community health workers or nurses in delivering care. Despite the positive outcomes, several limitations were identified, including short follow-up periods, small sample sizes, lack of randomization, and challenges related to program sustainability and generalizability. This review highlights the importance of context-specific, community-centered strategies for addressing hypertension among rural populations. It provides policymakers, nursing educators, and healthcare practitioners with insights to develop scalable, evidence-based agronursing programs. Further research is needed to assess the long-term impact of these interventions and their integration into national rural health systems.